KOMUNIKASI INTERPERSONAL PASANGAN SUAMI ISTRI PASCA KELAHIRAN ANAK PERTAMA - Maulida, Safiera; Kusumaningtyas, Ratri (Jurnal Common, 2020)
The presence of children within family, especially the presence of the first child, is certainly not easy for young families, especially for women. In her first birth, a woman experienced different conditions such as changing roles and the responsibilities that must be carried out in her family is also increased. There is a need for self adjunction to face the new roles and activities especially in early weeks of babyborn, after a mother gave birth to a child. The method used in this study is a qualitative descriptive method. The respondents in this study were new families who had their first baby especially those who were postpartum and were not LDR (Long Distance Relationship). Samples will be used as interviewees in this study were 2 baby blues mother who employee and unemployee. Data analysis of this study using interactive analysis from Miles and Huberman. The results of this study showed that married couple conditions who have just got their first baby birth, especially mother who experienced the baby blues syndrome, certainly will experience a not so good conditions for the family and there is a need for good interpersonal communication to avoid conflicts that led a fatal outcome. Good interpersonal communication, fairness, empathy, mutual support, positive thinking and mutual respect for each other equality will develop a harmonious relationship between husband and wife in a family even though the mother who just gave birth experienced the baby blues syndrome. Keywords: Interpersonal Communication, Married Couple, First Child, Baby Blues Syndrome.